Moderators of the Effects of a Digital Parenting Intervention on Child Conduct and Emotional Problems Implemented During the COVID-19 Pandemic: Results From a Secondary Analysis of Data From the Supporting Parents and Kids Through Lockdown Experiences (SPARKLE) Randomized Controlled Trial - Nikola Pokorna; Melanie Palmer; Oliver Pearson; Nicholas Beckley-Hoelscher; James Shearer; Katarzyna Kostyrka-Allchorne; Olly Robertson; Marta Koch; Petr Slovak; Crispin Day; Sarah Byford; Polly Waite; et al. (JMIR Publications, 2024)
BackgroundA smartphone app, Parent Positive, was developed to help parents manage their children's conduct and emotional problems during the COVID-19 pandemic. A randomized controlled trial, Supporting Parents and Kids Through Lockdown Experiences (SPARKLE), found Parent Positive to be effective in reducing children's emotional problems. However, app effectiveness may be influenced by a range of child, family, socioeconomic, and pandemic-related factors. ObjectiveThis study examined whether baseline factors related to the child, family, and socioeconomic status, as well as pandemic-related disruption circumstances, moderated Parent Positive's effects on child conduct and emotional problems at 1- and 2-month follow-up. MethodsThis study was a secondary exploratory analysis of SPARKLE data. The data set included 646 children (4-10 years of age) with parents randomized to either Parent Positive (n=320) or follow-up as usual (n=326). Candidate baseline moderators included child age, gender, attention-deficit/hyperactivity disorder symptoms, parental psychological distress, family conflict, household income, employment status, household overcrowding, and pandemic-related disruption risk (ie, homeschooling, lockdown status, and isolation status). Child conduct and emotional problem outcomes measured at 1- (T2) and 2-months (T3) post randomization were analyzed using linear mixed-effects analysis of covariance models adjusting for baseline (T1) measure of outcome and including intervention and intervention by time point interaction terms allowing for different effects at the 2 time points. Moderation of intervention effects by baseline factors was assessed by replacing the intervention by time interaction terms with intervention by time point by baseline moderator interaction terms. ResultsChild gender was a significant moderator of the Parent Positive versus follow-up as usual effect on emotional problems (B=0.72, 95% CI 0.12-1.33; P=.02). Specifically, the effect of Parent Positive was close to significant (T2: B=-0.41, 95% CI -0.82 to 0.0004; P=.05) or significant (T3: B=-0.76, 95% CI -1.22 to -0.30; P<.001) in males only when compared with females, and males experienced a significantly larger reduction in emotional problems than females in the Parent Positive arm at the 2-month post randomization time point. None of the other investigated baseline factors moderated effects on emotional problems, and no factors moderated effects on conduct problems. ConclusionsThis study highlights Parent Positive's potential for effectively reducing emotional problems in primary school-aged male children across a wide range of families. However, due to limited variability in the demographic background of the families, cautious interpretation is required, and replications are necessary in diverse samples with longer follow-up times. Trial RegistrationClinicalTrials.gov NCT04786080; https://clinicaltrials.gov/ct2/show/NCT04786080